A Descriptive Study to Assess Knowledge and Attitude of Nursing Students Regarding Palliative Care and End of Life Care, at Selected Nursing Colleges, Faridkot Punjab - Kumar Sumeriya, Narendra; Saini, Hemant Kumar; Saini, Hemlata (Journal of Neonatal Surgery, 2025)
Aim: The study assesses the knowledge and attitude of nursing students toward palliative and end-of-life care in selected nursing colleges in Faridkot, Punjab. It aims to evaluate their understanding, perceptions, and readiness to provide compassionate care. Materials and methods: This study utilized a descriptive quantitative cross-sectional design with convenience sampling to recruit eligible nursing students from Faridkot, Punjab. Participants included BSc (N) 3rd, 5th, and 7th Sem students who consented, while 1stSem students were excluded due to limited clinical exposure to palliative and end-of-life care. Among 300 registered nursing students, the required sample size was 257, but 100 students completed the questionnaire. Data were collected through an online survey, ensuring voluntary, anonymous participation and confidentiality. A validated instruments were used: the PCQN to assess students’ knowledge of palliative care (20 items, scoring range 0–20, reliability 0.68)and FATCOD Form B Scales (5-point Likert scale, 9 items, score range 9 – 45, reliability 0.70)was used to assess student’sattitudes towards dying patients. Demographic data, including age, gender, GPA, academic year, prior education or training in palliative care, experiences with dying patients, and involvement in end-of-life care, were also collected. Data analysis was done using SSPS software. Results: The study included a total of 100 participants, with 16% being male and 84% female. Regarding age, 37% of the participants were 20 years old or younger, while 63% were older than 20 years. In terms of their academic Sem., 37% were in their 3rd Sem, 33% in their 5th Sem, and 30% in their 7th Sem. The distribution of cumulative grade point averages showed that 23% had scores between 60–69.9%, 24% between 70–79.9%, 20% between 80–89.9%, and 33% had scores of 90% or higher. When asked about palliative care education, 67% reported receiving lectures or training on the subject, while 33% had not. Only 14% of participants had seen or witnessed a dying patient, whereas 86% had not. Additionally, 46% had cared for a family member or relative in their last days of life, while 54% had not. Lastly, 56% of participants had prepared or participated in the preparation of dead patients, whereas 44% had no such experience. Conclusion: The study revealed that nursing students in Faridkot, Punjab, had inadequate knowledge of palliative care but held a positive attitude toward end-of-life care. Incorporating palliative care education into nursing curricula is crucial to improving their understanding and preparedness.